Carbon management: Evidence from case studies of German firms under the EU ETS - Peter Heindl; Benjamin Lutz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper examines the management practices of German firms with obligations under the EU Emissions Trading Scheme (EU ETS) based on six structured in-depth interviews with managers of firms from different industries and based on survey data. The paper sheds light on management and trading practices, abatement behaviour, and the impact of the EU ETS on long-term decisions, such as investment decisions or innovative capacity. The aim is to provide information on firm-internal management processes related to the EU ETS and to strengthen intuition for microeconomic consequences of greenhouse gas regulation in a cap-and-trade scheme. The analysis reveals that management practices in the EU ETS are mainly driven by emission levels, firm size, pre-existing management structures and production patterns. While larger emitters (about 100,000 tCO2 per year or larger) are perfectly capable to carry out all relevant tasks, smaller emitters behave more passively due to transaction costs and lower expected return of transactions. Our analysis suggests that institutional responds to regulation should be taken into account for the design of greenhouse gas regulation.
urn:nbn:de:bsz:180-madoc-327560
Keywords: L60; Q50; M11; 330; Carbon Management; Emissions Trading; EU ETS; Luftverunreinigung; Kohlendioxid; Management; Unternehmenspolitik; Emissionshandel; EU-Europäisch; Deutschland; EU-Staaten